Synthesis of Pyranopyrans from Carbohydrates - M. Giuliano, Robert (Current Organic Chemistry, 2014)
Carbohydrates have been utilized as starting materials for the synthesis of pyranopyrans, which are important building blocks for the total synthesis of polyethers and other natural products. This review focuses on the synthesis of pyranopyrans from carbohydrates, with emphasis on the stereoselective functionalization of sugars and on the methods used to construct additional rings onto a carbohydrate template. Anhydro sugars, deoxy sugars, lactones, glycals, glycosides and other derivatives of carbohydrates have been used as starting materials for the synthesis of natural products such as ansamycins, halichondrin B, okadaic acid, dactomelynes, thyrsiferol, and polyethers brevetoxin A, ciguatoxin, and brevisin. Methods for ring closure are covered and show a progression toward the increased use of metal-catalyzed processes.
Keywords: pyranopyrans